Perceived effects of transhumant practices on natural resource management in southern Mali - Umutoni, Clarisse; Ayantunde, Augustine A. (Springer, 2018)
Recurring forage and water scarcity in the Sahelian zone of West Africa, especially in the dry season, has led to increased livestock movement into Sudano-Sahelian and Sudano-Guinean zones in the region. This increased movement by transhumant herders has resulted in growing competition over natural resources. Despite the strong presence of transhumant herds in the Sudano-Sahelian/Sudano-Guinean zones of Mali in the past 30 years, there has been limited research on the practice of transhumance in these zones, compared to several studies in the Sahelian zone. In this paper, we present how various actors in two districts in the Sudano-Sahelian/Sudano-Guinea zones of Mali perceived the effect of transhumant practices on natural resource management. Results from the study showed that more than 75% of all categories of respondents in both study sites perceived a decline in availability of forage resources and water as a result of the increased number of transhumant herders in their communities. Furthermore, a greater proportion of farmers and settled pastoralists in both study sites responded that there has been a decline in species richness of the vegetation. In contrast, more than 50% of transhumant herders did not see any change in species richness of natural vegetation due to their presence. They argued that the observed decline in species richness of the vegetation is due to climate change. Education level, location and socio-professional categories tended to be the key factors influencing respondent’s perception on the impact of transhumant practices on natural resource management. As the perceived impact of transhumant practices depends on socio-professional groups, it is necessary to engage all the actors on how to effectively manage the presence of transhumant herders, in order to promote sustainable use of natural resources in southern Mali. Besides, more research is needed to assess the validity of the reported perceptions in this study.